Invasive wild deer exhibit environmental niche shifts in Australia: Where to from here? - Catherine L. Kelly; Iain J. Gordon; Lin Schwarzkopf; Anna Pintor; Anthony Pople; Ben T. Hirsch (Ecology and Evolution)
Abstract Invasive species have established populations around the world and, in the process, characteristics of their realized environmental niches have changed. Because of their popularity as a source of game, deer have been introduced to, and become invasive in, many different environments around the world. As such, deer should provide a good model system in which to test environmental niche shifts. Using the current distributions of the six deer species present in Australia, we quantified shifts in their environmental niches that occurred since introduction; we determined the differences in suitable habitat between their international (native and invaded) and their Australian ranges. Given knowledge of their Australian habitat use, we then modeled the present distribution of deer in Australia to assess habitat suitability, in an attempt to predict future deer distributions. We show that the Australian niches of hog (Axis porcinus), fallow (Dama dama), red (Cervus elaphus), rusa (C. timorensis), and sambar deer (C. unicolor), but not chital deer (A. axis), were different to their international ranges. When we quantified the potential range of these six species in Australia, chital, hog, and rusa deer had the largest areas of suitable habitat outside their presently occupied habitat. The other three species had already expanded outside the ranges that we predicted as suitable. Here, we demonstrate that deer have undergone significant environmental niche shifts following introduction into Australia, and these shifts are important for predicting the future spread of these invasive species. It is important to note that current Australian and international environmental niches did not necessarily predict range expansions, thus wildlife managers should treat these analyses as conservative estimates.